CONCEPTS AND INDEPENDENCE UNDERSTANDING ANALYSIS STUDENTS LEARN MATHEMATICS ON THE MATERIAL CLASS IX SQUARE EQUATIONS AND FUNCTIONS STATE JUNIOR HIGH SCHOOL 3 ONOLALU - Laia, Asri Yanti (Universitas Nias Raya, 2023)
This study aims to describe the ability to understand concepts and determine the independence of class IX students of SMP Negeri 3 Onolalu in solving equations and quadratic functions. This research was conducted at SMP Negeri 3 Onolalu in class IX. The method used in this research is a qualitative research method, with a descriptive approach. 21 students of class IX at SMP Negeri 3 Ono were then used as research subjects. The instruments used in this study were tests of students' ability to understand concepts, questionnaires for student learning independence, and interviews. Based on the research findings, it was concluded that out of 21 students, 1 student (4.76%) had the ability to understand mathematical concepts in the very good category, 3 students (14.28%) had the ability to understand mathematical concepts in the good category, 6 students (28.57%) had the ability to understand mathematical concepts in the moderate category, 7 students (33.33%) had the ability to understand mathematical concepts in the poor category, and 4 students (19.04%) had the ability to understand mathematical concepts. very bad category. In addition, based on the research findings, it was found that out of 21 students, 1 student (4.76%) had a level of learning independence in the very independent category, 3 students (14.29%) had a level of learning independence in the independent category, 3 students (14.29%) had a level of learning independence in the moderately independent category, 11 students (52.38%) had a level of learning independence in the less independent category, and 3 students (14.29%) had a level of learning independence in the very less independent category.